(untitled) (Bioagro, 2022)
Cocoa (Theobroma cacao L.) is one of the most important crops in Ecuador; however, its production is limited, among other factors, by the crop nutrition. The objective of this research was to determine the effect of the combined nitrogen, phosphorus and potassium fertilization on soil characteristics, growth traits and quality of shoots and fruits in cocoa. The experiment was carried out under a completely randomized design with factorial arrangement, with three factors, N, P and K, and two levels by factor (with and without fertilization), plus an absolute control without fertilization. The chemical characteristics of the soil, including pH, N, P, K, Ca and Mg content were evaluated. New shoots were also evaluated by measuring its number, length, leaf area, and growth rate. In the fruits, the weight, length and growth rate were measured. In shoots and fruits, quality traits including dry matter, fiber, ash, lipids and protein content were measured. Significant interactions of the applied nutrients were found, which increased the content of P and K, and decreased Ca and Mg of the soil. The N fertilization alone did not affect the growth of the shoots and foliar area. The interactions of the primary elements significantly increased the dry matter and fiber of the shoots, while the growth and quality of fruits were not modified.